Vaginal delivery of mucus-penetrating organic nanoparticles for photothermal therapy against cervical intraepithelial neoplasia in mice. Issue 29 (1st July 2019) - Wang, Xue; Fu, Li; Lin, Wenhai; Zhang, Wei; Pei, Qing; Zheng, Xiaohua; Liu, Shi; Zhang, Tao; Xie, Zhigang
Abstract : Photosensitizer-based photothermal therapy (PTT) may be a good choice for the treatment of severe cervical intraepithelial neoplasia (CIN) compared with conventional thermal ablation. Abstract : Photosensitizer-based photothermal therapy (PTT) may be a good choice for the treatment of severe cervical intraepithelial neoplasia (CIN) compared with conventional thermal ablation. Vaginal delivery of photosensitizers is helpful to reach the maximal accumulation of photosensitizers in the lesion site but the penetration of drug through the mucus layer remains problematic. Boron-dipyrromethene (BODIPY or BDP) is one kind of highly stable and versatile organic dye. In the present study, we developed mucus-penetrating poly(ethylene glycol)–BDP nanoparticles (PEG–BDP/NPs) by using a solvothermal method, which is different from traditional protocols, such as amphiphilic copolymer encapsulation or covalent bonding of PEG. The results showed that PEG–BDP/NPs were much superior to BDP-loaded methoxy (polyethylene glycol)- b -poly(l -lactide) (MPEG–PLLA) micelles (BDP/M) in both cellular uptake and mucus penetration in vitro and in vivo . Then, the PEG–BDP/NPs with a high photothermal conversion efficiency of 48.3% were infused into the vaginas of mice with mock CIN for PTT. Although the nanoparticles couldn't selectively be accumulated in the CIN lesion, accurate location of laser irradiation, ultralow laser intensity and great biocompatibility of the nanoparticles enabled great efficacy and safety to be achieved. Therefore, the mucus-penetrating PEG–BDP/NPs with PTT capacity represent a promising approach for the treatment of severe CIN, and this work opens doors toward practical application of phototherapy.